The Effect of Organic Waste Potential of Mersin and Adana Provinces on Biogas Energy Production - Yelmen, B.; Cakir, M.T. (Journal of Environmental Science and Engineering Technology, 2019)
In this study, the current state of organic wastes obtained from plant, animal, kitchen and industrial sewage sludge plants in Mersin and Adana provinces and biogas energy production potential were investigated. In this study, data on animals and plants were obtained from Adana and Mersin Provincial Directorate of Agriculture and data on kitchen and industrial wastes were obtained from Adana and Mersin Metropolitan Municipality. As a result of this study, the daily amount of organic matter produced in animal, vegetable, kitchen and sewage sludge plants in Mersin province is 16 801.48 tons and the amount of biogas produced from these wastes is 557 432.47 m3 and the electricity generated from methane is 2 619.93 MWh. It has been identified. In Adana province, the daily organic matter produced in animal, vegetable, kitchen and sewage sludge plants is 24 517.35 tons and the amount of biogas produced from these wastes is 637 882.68 m3 and the electricity generated from methane is 2 998.05 MWh. In Mersin, 33% of the electricity generated from organic wastes was obtained from treatment sludge, 57% from animal manure, 4% from agricultural waste and 6% from kitchen waste. In Adana, 39% of the electricity generated from organic wastes was obtained from treatment sludge, 36% from animal manure, 15% from agricultural wastes and 10% from kitchen wastes. Adana Province; In terms of organic matter produced in animal, vegetable, kitchen and sewage sludge plants, it is determined that it is approximately 19% more than Mersin province and it is about 7% more in terms of electrical energy produced from methane.